The Role of the Internal Audit Department In the Effectiveness of Governance in the Public Sector: An Applied Study on the Ministry of National Guard In the Kingdom of Saudi Arabia - Al-Dosari, Fahd; B. Haddad, Muhammad (The Arab Journal of Administration, 2023)
This study aimed to identify the internal audit department and its impact on activating governance in the Ministry of National Guard. It also aimed to define the internal audit department, its roles and responsibilities in the Ministry of National Guard, and define governance and its current level in the Ministry of National Guard. As well as the definition of the role and tasks of the internal audit department in the effectiveness of governance. The definition of the relationship between the efficiency of the human element and the uses of technology in the effectiveness of governance. The study used the descriptive analytical approach, and the questionnaire was used as a tool for the study. The sample size is (120) individuals. Among the most important findings of the study, the results of the study showed that there is clarity of roles and responsibilities and the effectiveness of governance in the Ministry of National Guard, that: The internal audit unit contributes to assessing the potential financial and non- financial risks that the ministry may face and develop appropriate plans to deal with them, there is a relationship between the efficiency and specialization of the human element and the effectiveness of governance, The internal audit team performs functional activities and duties from a constructive perspective that aims to improve and control daily operations. The internal audit unit benefits from technology applications and e-government at the Ministry of National Guard. The efficient impact of technology applications and e-government affects governance at the Ministry of National Guard. One of the most important recommendations made The researcher reached it: working on the need to clarify the job roles of the Ministry’s employees, which is considered one of the tasks of the internal audit unit, Providing recommendations and consultations by the Internal Audit Unit to the concerned departments on a regular basis that contributes to improving practices and controlling internal operations, and this in turn reduces abuses and violations. The necessity of prior planning for the internal audit process in order to make the audit process successful in the Ministry. The need to make more efforts by the National Guard in order to optimize the use of e-government applications. This contributes to improving internal auditing.